An EMI filter design method based on improved Foster network model for Boost PFC converter. (December 2020) - Chen, Dongdong; Lin, Yanqiang; Xiao, Long
Abstract: In this paper, the problem of conducted electromagnetic interference in Boost PFC converters is studied, through the analysis of its common-mode and differential-mode interference conduction paths in Boost PFC converters with or without the balanced capacitor, the causes and suppression methods of mixed-mode conducted electromagnetic interference in Boost PFC converters are studied. The core material frequency parameter characteristics and winding parasitic capacitors are added to analysis to build more accurate models, the non-linear parameter characteristics of choke impedance and the disadvantage of traditional Foster network model are researched. Moreover, this paper proposed a series model based on improved Foster network, and design an EMI filter based on proposed improved Foster network with the optimized high-frequency characteristics. Experiments were carried out using a prototype of a built Boost PFC converter. The results show that after the EMI filter with proposed designed method was added to the circuit, the prototype under test can successfully pass the corresponding EMI test. It indicates the effectiveness of the proposed method.